Gendered Cultural Differences and Change in Gender Roles Among Displaced Refugees. (October 2019) - Daniely, Dvora Lederman; Lederman, Shmuel
This article examines the emancipatory potential, which exists in displacement in terms of the change in gender roles and the transformation of women into influential and leading forces in the rehabilitation of refugees. It also examines the issue from a cultural archetypal point of view and investigates the cultural interpretation and perception of the state of chaos and destruction as gender-dependent. On the basis of archetypal models of rites of passage, we examine the different perceptions of the liminal and anti-structural phase of displacement and the way it diminishes powers and coping resources among men, as opposed to the creation of healing and rehabilitative resources derived from the marginal areas of women's culture.